2019
DOI: 10.1155/2019/9024258
|View full text |Cite|
|
Sign up to set email alerts
|

Inadequate Prenatal Visit and Home Delivery as Determinants of Perinatal Outcomes: Does Parity Matter?

Abstract: Background. Adverse perinatal outcomes are still high in developing countries. Contradicting evidences were reported about the effect of parity on adverse perinatal outcomes. The aim of this study was to compare perinatal outcomes in grand multiparous and low multiparity women in Hawassa University Comprehensive Specialized Hospital and Adare General Hospital of Ethiopia. Methods. Comparative cross-sectional study design was employed to include 461 mothers from February to June 2018. Data were collected by str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Prematurity, low birth weight, stillbirth, and congenital malformations constitute some of the common adverse birth outcomes. 1 Globally, an estimated 2.6 million stillbirths occurred each year, one in every 16 seconds. Ninety-eight percent of these deaths occurred in low-and middle-income countries and 75% in Sub-Saharan Africa and Southern Asia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prematurity, low birth weight, stillbirth, and congenital malformations constitute some of the common adverse birth outcomes. 1 Globally, an estimated 2.6 million stillbirths occurred each year, one in every 16 seconds. Ninety-eight percent of these deaths occurred in low-and middle-income countries and 75% in Sub-Saharan Africa and Southern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…This study also found a higher prevalence of stillbirth (38.9%), low APGAR score (51.9%), and low birth weight (40.7%) among grand multiparous women, while a higher risk of meconium aspiration (9.8%), need for resuscitation (14.7%), and macrosomia (57.4%) among low multiparous women. 1 Contradicting evidence across studies was reported about the impact of grand multiparity on adverse perinatal outcomes. In Tanzania, meconium-stained amniotic fluid and low APGAR (Appearance, Pulse, Grimace, Activity, and Respiration) scores were significant among neonates born to grand multiparous women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unplanned pregnancy has been linked to a poor QOL, less antenatal care, and risky behaviors [ 29 ]. Less or inadequate antenatal care has been associated with adverse perinatal outcomes, such as stillbirth and congenital malformation [ 30 ]. Generally, antenatal care is a primary intervention that contributes in decreasing maternal morbidity and mortality [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the article titled “Inadequate Prenatal Visit and Home Delivery as Determinants of Perinatal Outcomes: Does Parity Matter?” [1], Dr. Abel Gedefaw was missing from the authors' list. Dr. Abel Gedefaw contributed to the proposal development and the article's draft.…”
mentioning
confidence: 99%